Measurable Differences between Sequential and Parallel Diagnostic Decision Processes for Determining Stroke Subtype: A Representation of Interacting Pathologies - Helgason, Cathy M.; Watkins, Fred A.; Jobe, Thomas H. (Thrombosis and Haemostasis, 2002)
Stroke diagnosis depends on causal subtype. The accepted classification procedure is a succession of diagnostic tests administered in an order based on prior reported frequencies of the subtypes. The first positive test result completely determines diagnosis. An alternative approach tests multiple concomitant diagnostic hypotheses in parallel. This method permits multiple simultaneous pathologies in the patient. These two diagnostic procedures can be compared by novel numeric criteria presented here.Thrombosis, a type of ischemic stroke, results from interaction between endothelium, blood flow and blood components. We tested for ischemic stroke on thirty patients using both methods. For each patient the procedure produced an assessment of severity as an ordered set of three numbers in the interval [0, 1]. We measured the difference in diagnosis between the sequential and parallel diagnostic algorithms. The computations reveal systematic differences: The sequential procedure tends to under-diagnose and excludes any measure of interaction between pathologic elements.
Keywords: Stroke subtype; diagnosis; pathogenesis; cause; interaction; ischemic stroke